Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper for Indonesia reports that following the major cleanup of the banking sector after the crisis, banks' performance has improved as net interest margins and profitability have increased. Public and external debt ratios have declined and international reserves have risen, reducing domestic and external vulnerabilities. Indonesia stands out as having experienced a slower recovery in investment and exports than other countries hit by the Asian crisis. Recognizing the challenge, the government has adopted a sound medium-term strategy focused on boosting economic growth.